Competency Development Strategy for Government Internal Supervisory Apparatus (GISA) within the Regional Government of West Maluku Regency - Evrina Reiper; Hamka Hamka; Mala Sondang Silitonga (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this research is to determine the competence of the Government Internal Supervisory Apparatus (GISA) within the Regional Government of Southwest Maluku Regency, and to develop a strategy for developing the competence of the Government Internal Supervisory Apparatus (GISA) within the Government of Southwest Maluku Regency. The research method that researchers use in conducting this research is a descriptive research method with a qualitative approach. The results showed that the competence of the Government Internal Supervisory Apparatus (GISA) within the Regional Government of Southwest Maluku Regency has high motivation in carrying out the duties of the position, as seen from the services provided to auditees. However, the opportunity to participate in self-development is not yet in accordance with the duties of the position. New tasks or jobs are completed based on GISA motivation. The average GISA HR has a good nature, not easily influenced by the environment. Eager to carry out tasks, do not compromise with personal policies from the auditee. Self-concept, character and motivation are hidden in each person and are difficult to develop through training programs, but will be formed and developed from the length of time a person carries out certain tasks. The longer GISA HR occupies a supervisory position can help him to get better. However, to know the auditee's personality, GISA needs special training related to psychology. In general, GISA's knowledge is quite good, but specifically GISA's knowledge related to their job duties is still lacking, development is needed for each individual GISA. The skills dimension relates to technical competence. The development of technical competence for GISA on a regular basis is able to create GISAs who are skilled in carrying out their duties. Competency development strategies that have been carried out for GISA in Southwest Maluku Regency by conducting professional skill training, job enrichment, comparative studies, and building teamwork.